Unveiling the Roots and Ripple Effects of Banditry in Katsina State: A Deep Dive into Causes and Consequences - Atiyaye, Dauda Mohammed; Kaku, Mohammed; Kele, Ali; Cheri, Lawan; Goni, Umar Mohammed (Kashere Journal of Politics and International Relations, 2025)
This study explores the underlying causes and far-reaching effects of banditry in Katsina state, with a particular focus on the perspectives of local communities through qualitative methodologies. Using in-depth interviews and focus group discussions (FGDs) involving community members, stakeholders, and security personnel in Danmusa, Kankara, Batsari and Jibia Local government areas, this research aims at understanding the factors driving banditry and its social, economic, and psychological impacts. The qualitative approach enable the collection of rich, descriptive data, revealing the complexity of the issues beyond what factors contribute to the rise of banditry in Katsina state. Drug abuse emerged as a major catalystthat triggers criminal activities. Bad governance seemed a fertile reason for bandit groups to thrive. Furthermore, inter-tribal mistrust rooted in the longstanding farmers-herders conflict has exacerbated tensions, particularly between the Fulani nomadic herders and Hausa sedentary farmers. This mistrust, often ignited by competition over land and water resources, has led to communal strife, further destabilizing the region. The consequences of banditry are profound including kidnapping and displacement of communities to the disruption of agricultural activities, which form the backbone of local economy. The study also found significant psychological impacts, with many residents living in a constant state of fear and insecurity. Addressing the root causes requires a comprehensive approach, including strengthening governance, promoting dialogue between communities, and providing youth-oriented programs to curb drug abuse. This research highlights the need for policymakers and stakeholders to address the multi-faceted drivers of banditry to ensure sustainable peace and development in Katsina state.